2014
DOI: 10.1002/cbin.10322
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4‐dependent cellular response does not relate to CYP3A4‐catalysed metabolites of C‐1748 and C‐1305 acridine antitumor agents in HepG2 cells

Abstract: High CYP3A4 expression sensitizes tumor cells to certain antitumor agents while for others it can lower their therapeutic efficacy. We have elucidated the influence of CYP3A4 overexpression on the cellular response induced by antitumor acridine derivatives, C-1305 and C-1748, in two hepatocellular carcinoma (HepG2) cell lines, Hep3A4 stably transfected with CYP3A4 isoenzyme, and HepC34 expressing empty vector. The compounds were selected considering their different chemical structures and different metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Based on the liquid chromatography mass spectrometry (LC-MS) data ( Figure 3), two metabolites were predicted to be 1-amino-9-hydroxyethylaminoacridine (M1) and 1nitroacridinone (M2), mammalian metabolites were also previously reported [15,20]. In contrast to the metabolism of the studied compound in human hepatocellular carcinoma cell lines under normoxia, the metabolites profile observed in C. albicans seems to be similar to that obtained for mammalian cells under hypoxia or reducing conditions [15,20]. The main fungal metabolic product M1 (m/z 268.1), 1-amino-9hydroxyethylaminoacridine was detected as the main metabolic product of human cancer cell lines only under a low level of oxygen.…”
Section: Biotransformation Of Capridine β In Fungal Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on the liquid chromatography mass spectrometry (LC-MS) data ( Figure 3), two metabolites were predicted to be 1-amino-9-hydroxyethylaminoacridine (M1) and 1nitroacridinone (M2), mammalian metabolites were also previously reported [15,20]. In contrast to the metabolism of the studied compound in human hepatocellular carcinoma cell lines under normoxia, the metabolites profile observed in C. albicans seems to be similar to that obtained for mammalian cells under hypoxia or reducing conditions [15,20]. The main fungal metabolic product M1 (m/z 268.1), 1-amino-9hydroxyethylaminoacridine was detected as the main metabolic product of human cancer cell lines only under a low level of oxygen.…”
Section: Biotransformation Of Capridine β In Fungal Cellsmentioning
confidence: 94%
“…The elution of sample components were monitored at 380 nm, as it has been shown previously for C-1748 and its metabolites in HepG2 cells [15,20] and at 420 nm.…”
Section: Chromatographic Analysismentioning
confidence: 99%
“…Moreover, the metabolic profiles of C-1305 and C-1311 were not changed in MCF-7 and HCT116 cells after their overexpression with P4503A4 isoenzyme [47]. Thus, P4503A4 does not take part in the metabolism of studied acridinone derivatives, as we previously showed with recombinant isoenzymes in a non-cellular system [26,27] and in HepG2 cells [29,31]. EV.…”
Section: Metabolic Transformation Of C-1305 and C-1311 In Mcf-7 And Hmentioning
confidence: 60%
“…Each compound was also found to be metabolized with human recombinant flavin-containing monooxygenases 1 and 3 (FMO1, FMO3) [27,28]. Although the metabolism of both studied drugs did not depend on P4503A4 expression, the cellular response, including apoptosis, was stronger in P4503A4-overexpressing HepG2 and CHO cells following C-1305 [29,30] and C-1311 [31,32] treatment. It was also demonstrated that the studied compounds underwent UGT-mediated metabolism to 8-O-glucuronides with human liver and intestinal microsomes and particularly with recombinant extrahepatic UGT1A10 isoenzyme [33].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, another study showed that C‐1305 strongly induced the activity and expression of CYP3A4 and CYP2C9, as well as expression of UDP‐glucuronosyltransferase (UGT) 1A1 and MDR1 in pregnane X receptor‐dependent HepG2 cells 24,25 . Overexpression of CYP2A4 enhanced the apoptosis induced by C‐1305 or C‐1311 in CHO cells 26,27 . Some authors suggest that extrahepatic UGT1A10 also plays an important role in the metabolism and bioactivation of C‐1305, and this biotransformation leads to enhanced proapoptotic activity of these glucuronide products 28,29 .…”
Section: Discussionmentioning
confidence: 99%